McIsaac criteria for diagnosis of acute group-A β-hemolytic streptococcal pharyngitis - Imanuel Y. Malino; Dwi Lingga Utama; Yati Soenarto (Paediatrica Indonesiana, 2013)
Background The early use of antibiotics for acute upper respiratory infections is controversial because most of these infections are caused by viruses. A strategy is needed to correctly identify the causitive agents of acute pharyngitis, so that antibiotics can be prescribed appropriately.Objective To assess McIsaac criteria for diagnosing acute group-A β-hemolytic streptococcal (GABHS) pharyngitis in children.Methods This diagnostic study was conducted from August 2011 to February 2012, to compare clinical criteria of McIsaac to throat swab culture results as the gold standard for diagnosis. Subjects were children aged 3-14 years who visited the pediatric outpatient clinic or emergency ward at Sanglah Hospital and the pediatric outpatient clinic at Wangaya Hospital.Results There were 550 cases of acute pharyngitis during the study period, with 313 patients aged 3-14 years and 199 patients excluded due to a history of taking antibiotics in the two weeks prior to the hospital visit. Hence, 114 subjects were eligible for the study. GABHS prevalence in this study was 7.9%. McIsaac’s area under the curve (AUC) from receiver operating characteristic (ROC) curve was 78.1%(95%CI 60.3 to 96%, P= 0.005). A McIsaac score ≥4 had a 66.7% (95%CI 49 to 97%) sensitivity, 87.6% (95% CI 81 to 94%) specificity, 31.6% (95 %CI 11 to 52%) positive predictive value (PPV), 96.8% (95%CI 93 to 100%) negative predictive value (NPV), 86.0% accuracy, 5.4 (95% CI 2.7 to 10.7) positive likelihood ratio (LR+) and 0.4 (95% CI 0.2 to 0.9) negative likelihood ratio (LR-).Conclusion A McIsaac criteria total score of <4 is favorable for excluding a diagnosis of GABHS pharyngitis. A McIsaac total criteria score of ≥4 requires further examination to confirm a diagnosis of GABHS pharyngitis.